Preparation of synthetic polymer from plastic waste using sulphur dioxide - Kishore, Kannan (2010)

(untitled)
The synthesis of polymer using sulphur dioxide gas is being studied in this research. The objective of this research is to obtain a new synthetic polymer that contains hydrophilic property. This research also contributes towards sustaining the green environment because we recycle the waste. High density polyethylene (HDPE) polymer and sulphur dioxide gas were used in this research. The reaction between HDPE and sulphur dioxide will yield a new synthetic polymer that contains hydrophilic property and biodegradable. The functional group of the product which is sulfonic acid was identified by using Fourier Transform Infrared spectrometer (FTIR). The synthetic polymer might be a potentially valuable source as a fabric, for the usage of chemical feed stocks and also material for membrane technology.